All in One, Self‐Powered Bionic Artificial Nerve Based on a Triboelectric Nanogenerator - Zhang, Qian; Zhang, Zixuan; Liang, Qijie; Shi, Qiongfeng; Zhu, Minglu; Lee, Chengkuo (Advanced science, 2021)
Sensory and nerve systems play important role in mediating the interactions with the world. The pursuit of neuromorphic computing has inspired innovations in artificial sensory and nervous systems. Here, an all‐in‐one, tailorable artificial perception, and transmission nerve (APTN) was developed for mimicking the biological sensory and nervous ability to detect and transmit the location information of mechanical stimulation. The APTN shows excellent reliability with a single triboelectric electrode for the detection of multiple pixels, by employing a gradient thickness dielectric layer and a grid surface structure. The sliding mode is used on the APTN to eliminate the amplitude influence of output signal, such as force, interlayer distance. By tailoring the geometry, an L‐shaped APTN is demonstrated for the application of single‐electrode bionic artificial nerve for 2D detection. In addition, an APTN based prosthetic arm is also fabricated to biomimetically identify and transmit the stimuli location signal to pattern the feedback. With features of low‐cost, easy installation, and good flexibility, the APTN renders as a promising artificial sensory and nervous system for artificial intelligence, human–machine interface, and robotics applications. An all‐in‐one, tailorable artificial perception, and transmission nerve is developed for mimicking the biological sensory and nervous ability to detect and transmit the location information of mechanical stimulation. The as‐mentioned process consumes no electrical energy at all. In addition to detecting 2D stimuli by a single‐electrode mode, a self‐powered prosthetic arm is also demonstrated.